The RNA Polymerase II Trigger Loop Functions in Substrate Selection and is Directly Targeted by α-amanitin - Kaplan, Craig D. (2008)
Structural, biochemical and genetic studies have led to proposals that a mobile element of multi-subunit RNA polymerases, the Trigger Loop (TL), plays a critical role in catalysis and can be targeted by antibiotic inhibitors. Here we present evidence that the Saccharomyces cerevisiae RNA Polymerase II (Pol II) TL participates in substrate selection. Amino acid substitutions within the Pol II TL preferentially alter substrate usage and enzyme fidelity, as does inhibition of transcription by α-amanitin. Finally, substitution of His1085 in the TL specifically renders Pol II highly resistant to α-amanitin, indicating a functional interaction between His1085 and α-amanitin that is supported by re-refinement of an α-amanitin-Pol II crystal structure. We propose that α-amanitin inhibited Pol II elongation, which is slow and exhibits reduced substrate selectivity, results from direct α-amanitin interference with the TL.